The Effectiveness of Project-Based Learning in Improving Reading Literacy Among Fifth-Grade Students with Dyslexia - Irwanto, Doli; Pamungkas, Bayu (Papanda Publisher, 2025)
Dyslexia affects 5-15% of elementary students globally, yet traditional instructional methods often inadequately address their unique learning needs. Project-based learning (PBL) has shown promise for diverse learners, but its effectiveness for dyslexic students remains underexplored. This study evaluated the impact of project-based learning interventions on reading literacy development among dyslexic fifth-grade students. A classroom action research design using the Kemmis and McTaggart model was implemented at SD Negeri 008 Muara Bengkal, involving three diagnosed dyslexic students as primary participants. The intervention consisted of two four-week cycles incorporating authentic reading tasks, collaborative activities, and multisensory approaches. Data collection included pre- and post-intervention reading assessments and structured classroom observations. Statistical analysis employed paired t-tests and effect size calculations, while qualitative data underwent thematic analysis. Participants demonstrated significant reading improvement with a mean gain of 32.33 points (Cohen's d = 2.89, p < 0.001), exceeding grade-level proficiency standards. Engagement indicators showed substantial increases: reading participation (42% to 85%), collaborative engagement (38% to 78%), and reading strategy use (25% to 78%). Classroom-wide improvements were also observed (72.8 to 90.0 mean score). Project-based learning effectively enhances reading literacy among dyslexic students when appropriately structured with explicit instruction and scaffolding, supporting inclusive educational practices and challenging assumptions about instructional approaches for learning disabilities.